2011
DOI: 10.1111/j.1460-2695.2011.01631.x
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue crack propagation into the residual stress field along and perpendicular to laser beam butt‐weld in aluminium alloy AA6056

Abstract: A B S T R A C T Laser beam butt welds in Al-alloys are very narrow and are accompanied by steep residual stress gradients. In such a case, how the initial crack orientation and the distance of the notch tip relative to the weld affect fatigue crack propagation has not been investigated. Therefore, this investigation was undertaken with two different crack orientations: along the mid-weld and perpendicular to the weld. Fatigue crack propagation 'along the midweld' was found to be faster in middle crack tension … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 40 publications
(187 reference statements)
2
11
0
Order By: Relevance
“…In these methods, FCGR data obtained by laboratory specimen tests are adopted for the life prediction of components based on the theory of linear elastic fracture mechanics (LEFM). Significant amount of research has been conducted in the past 20 years to understand the crack growth behaviours in welded joints . Some works indicate that changes in microstructure and hardness play a major role in the fusion zone or weld nugget and residual stress plays a major role outside these zones .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these methods, FCGR data obtained by laboratory specimen tests are adopted for the life prediction of components based on the theory of linear elastic fracture mechanics (LEFM). Significant amount of research has been conducted in the past 20 years to understand the crack growth behaviours in welded joints . Some works indicate that changes in microstructure and hardness play a major role in the fusion zone or weld nugget and residual stress plays a major role outside these zones .…”
Section: Introductionmentioning
confidence: 99%
“…Significant amount of research has been conducted in the past 20 years to understand the crack growth behaviours in welded joints. [4][5][6][7][8][9][10][11][12][13] Some works indicate that changes in microstructure and hardness play a major role in the fusion zone or weld nugget and residual stress plays a major role outside these zones. 10,13 Therefore, it is a common practice that only the primary influential factor is considered in crack growth analysis of welds; e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A comparison between the experimental and simulation results shows a good agreement. In 2012, Vaidya et al 10 studied the effect of crack orientation and the distance between the notch tip and the weld on fatigue crack propagation in a laser beam welded butt joint of the airframe Al-alloy AA6056. Fatigue crack propagation "along the midweld" was found to be faster in middle crack tension specimens than in compact tension specimens.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, much research was conducted on the fatigue property of aluminium alloy welds. Vaidya et al . investigated the fatigue crack growth (FCG) in laser beam welded aluminium alloy AA6056.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, much research was conducted on the fatigue property of aluminium alloy welds. Vaidya et al 3 investigated the fatigue crack growth (FCG) in laser beam welded aluminium alloy AA6056. The result showed that FCG in weld was faster than that in the base material when residual stress near the notch tip of the specimens was tensile.…”
mentioning
confidence: 99%